KEMAMPUAN BERTANYA DAN KEAHLIAN MEMBACA: KAJIAN PADA MAHASISWA NON-BAHASA INGGRIS UNIVERSITAS ISLAM LAMONGAN - Lilik Uzlifatul Jannah; Ike Susanti (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to determine the ability of students to formulate questions in English. This research employed descriptive qualitative method using simple analysis techniques based on grammatical and semantic analysis. Questions made by students are based on reading at the literal level or basic level. The research subjects involved 80 students in the Non-English Study Program in the second semester Management Study Program Lamongan Islamic University. The results of the study were obtained as follows (1). Students were able to formulate questions in English as many times, even if they do not meet the grammatical and semantic rules. (2). Students’ mistakes in formulating questions in English based on reading text including grammatical errors (60%) either errors in semantics or meanings (40%); and (3). Students still use translating techniques in formulating questions so that the strong influence of the use of the first language (Indonesian) and the rules of writing in the Indonesian language can be obviously seen. Finally, it can be concluded that the students’ reading skill is at the lower cognitive level or at literal phase.